Transitivity - Fishburn, Peter C. (Review of Economic Studies, 1979)
Journal Article Transitivity Get access Peter C. Fishburn Peter C. Fishburn Pennsylvania State University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 1, January 1979, Pages 163–173, https://doi.org/10.2307/2297179 Published: 01 January 1979 Article history Received: 01 February 1977 Accepted: 01 April 1978 Published: 01 January 1979